Revitalisasi Peran Guru PAI sebagai Agen Perdamaian di Tengah Polarisasi Sosial - Azka, Naily An Ngimatul; Nadhiroh, Yulsiva Anissatun; Salsabila, Nazma Tsania; Jannah, Mutia Miftachul (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This study aims to examine and revitalize the role of Islamic Religious Education (PAI) teachers as agents of peace in responding to increasing social polarization in Indonesian society. Using the literature review method, this study analyzes various relevant literature sources, ranging from peace theory, multicultural education, to the practice of religious moderation in the context of education. The results of the study indicate that PAI teachers have a strategic position in shaping the character of inclusive and tolerant students, but this role has not been optimized systematically in the curriculum or teacher professional training. The novelty of this study lies in the concrete mapping of the role of PAI teachers in five strategic domains: curriculum, school culture, role models, interfaith communication, and collaboration with the community. The implications of this study emphasize the importance of reformulating the PAI curriculum that is oriented towards peace values ??and strengthening teacher capacity through training that is integrated with the principle of religious moderation. This study is expected to be a contribution to the development of religious education that is adaptive to contemporary socio-cultural challenges